Nanoreinforced concrete composites for possible nuclear waste confinement a preliminary study - Mancini Maria Rita; Gattia Daniele Mirabile; Girardi Fabio; Ferri Donatella; Marzo Giuseppe A.; Masci Domenica (EPJ Web of Conferences, 2023)
Cementitious materials are the most abundant building materials even nowadays. Similarly, in the nuclear industry, concrete is the most used material for the confinement of radioactive waste, it has favorable properties, both chemical and physical, making it a desirable matrix for the encapsulation of radioactive and toxic wastes. Cemented wastes are preferred for the storage of a large varieties of fission products, such as low and intermediate level radioactive waste e.g., β—emitter 90Sr. Anyway, because of the intrinsic fragility of ordinary Portland Cement (OPC) a lot of efforts have been spent to enhance his mechanical resistance. Graphene Oxide (GO) represent an opportunity to overcome this problem. In fact, there is much evidence that GO can influence the toughness and the strength of the cement composites by regulating the morphology of the cement hydration products. 90Sr, the main strontium isotope in radioactive waste, is a by-product of the fission of uranium and plutonium in nuclear reactors. In this study we investigate the effects of strontium on mechanical properties of cement (OPC) and GO-reinforced cement. Different samples have been prepared with fixed concentration of GO. It has been observed that small quantities of GO, significantly [1] increases the compression strength of cement composites. The addition of Sr (65.0, 67.6 and 70.2 ppm) resulted in an increase of the compressive strength of 6.78%, 3.02% and 0.70% for those samples respectively, in comparison to OPC. Compression strength in samples of OPC with GO remained quite constant even in presence of Sr.